THANK YOU PROPHET - Masharipov Rachmatulla Beknazarovich (Journal of new century innovations, 2023)
Annotation: the main task in this article is to read fiction books in the reader mainly to inspire enthusiasm for reading the books of urine and religious and educational books, read to teach the daily conduct of his books, and to bless the Prophet sollallahu vasallam talks about further promotion.